1973
DOI: 10.1113/jphysiol.1973.sp010074
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of glomerular blood flow distribution in the new‐born dog

Abstract: SUMMARY1. Glomerular blood flow distribution was studied in seventy-eight new-born mongrel dogs aged 1-40 days by measuring the distribution of radioactive labelled microspheres within the kidney.2. The microsphere technique was found to be a valid indicator of glomerular blood flow distribution for the new-born dog since (a) the spheres were completely extracted by the kidney, (b) more than 95 % of the spheres were trapped in glomerular capillaries, (c) the spheres were evenly distributed within any specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
32
1

Year Published

1978
1978
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 12 publications
5
32
1
Order By: Relevance
“…of age. The present study demonstrates for the first time in lambs that the nephrogenic zone disappears around 130 days of gestation and that the total glomerular counts per kidney in fetuses over Previous studies (5,13,14,16) have demonstrated that the 130 days (4682% + 41173 glomeruli per kidney) is not significantly cortical blood flow is distributed preferentially to the juxtameduldifferent than in newborn lambs (433704 + 21553). Glomerular lary area of the cortex during early postnatal life, and with density, determined in four cortical zones (zone I being the out-maturation, the development of cortical flow follows a centrifugal ermost portion of the cortex) did not show any significant changes pattern.…”
supporting
confidence: 53%
“…of age. The present study demonstrates for the first time in lambs that the nephrogenic zone disappears around 130 days of gestation and that the total glomerular counts per kidney in fetuses over Previous studies (5,13,14,16) have demonstrated that the 130 days (4682% + 41173 glomeruli per kidney) is not significantly cortical blood flow is distributed preferentially to the juxtameduldifferent than in newborn lambs (433704 + 21553). Glomerular lary area of the cortex during early postnatal life, and with density, determined in four cortical zones (zone I being the out-maturation, the development of cortical flow follows a centrifugal ermost portion of the cortex) did not show any significant changes pattern.…”
supporting
confidence: 53%
“…In control animals (Group I), there were no effects of exchange transfusion with adult whole blood on hematocrit or any of the physiologic functions studied ( Table 1). The values for arterial blood pressure, renal hemodynamics and renal function in control animals are similar to values reported in newborn puppies in earlier studies (8,9). Results of the experimental group (Group 11) are presented with the baseline determination as control values for each animal.…”
Section: Resultssupporting
confidence: 73%
“…The kidneys were removed from the animal, weighed, allowed to dry overnight and then weighed and placed in a Packard auto gamma spectrometer and the radioactivity counted. These methods have been described in detail in an earlier paper (8). Although a relatively narrow range of spectral activity for-each isotope was chosen, complete separation of the isotopes was not achieved and crossover between the different isotopes was resolved by simultaneous equations.…”
Section: Speculationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been clearly established that renal growth (10,12,19,20,23) and functional maturation (2,13,14,17,22) proceed centrifugally. This is associated with the development of a progressively more superficial population of nephrons, and presents a potential obstacle to the investigation of maturation at the single nephron level.…”
Section: Discussionmentioning
confidence: 99%